Effectiveness of Android-Based 3D Applications to Support Students' Mental Models on Molecular Geometry Material - Putri Amalia Azzahra; Kurniawati, Yenni (Chemistry Education Department of Education and Teaching Faculty, 2024)
The learning media in the form of Android needs an effectiveness test to find out its effectiveness in material implementation at school. The purpose of this research was to find out the efficacy of 3D Android-based Based Chemistry Learning Media in molecule form material on students' mental models if compared to common learning media used at the school. This research was conducted at MA Darul Hikmah Pekanbaru. The research method used was a mixed method with the research design of The Explanatory Sequential Model. The samples were selected based on the technique of simple random sampling on grade X students of MA Darul Hikmah Pekanbaru. The research instrument used was a two-tier diagnostic test supported by interviews. The data were processed by using the hypothesis test and N-Gain test. The research results showed that overall, the student's mental model in the experimental group that used 3D Android Application Learning Media had 63% intact mental model and 37% alternative mental model. In comparison, students in the control group obtained 22% intact mental model and 78% alternative mental model. The research findings also showed the hypothesis test, which obtained sig. Value (2-tailed) = 0.000, which means 0.000<0.05 until Ha is accepted and Ho is rejected. Based on the N-Gain test, the experimental group showed quite an effective category, with the percentage of N-Gain amounted to 60%. This showed that media updates and material enrichment are required in order to increase the students' mental model.